Morphologic Heterogeneity in Carcinosarcoma of the Gallbladder: Report of a Rare Cases - Vani Krishnamurthy; Sheela Devi C. Shivalingiah; Sunila Ravishankar; Gubbanna V. Manjunath (Hindawi Limited, 2011)
Carcinosarcoma is a rare tumor composed of variable proportions of carcinomatous and sarcomatous elements and comprises less than one percent of all gallbladder malignancies. In most reported cases of carcinosarcoma of gallbladder, the epithelial component is adenocarcinoma. The mesenchymal component varies from homogenous sarcoma to more heterotopic elements like malignant bone, cartilage, and other mesenchymal tissues. We report a rare case of carcinosarcoma of the gallbladder in an 83-year-old male, with the carcinomatous component represented by undifferentiated carcinoma (spindle and giant cell type with osteoclastic giant cells) and the mesenchymal component seen as foci of chondrosarcoma.